Applied qualitative research design a total quality framework approach - Roller, Margaret R.; Lavrakas, Paul J. (New York The Guilford Press, 2015)
"This unique text provides a comprehensive framework for creating, managing, and interpreting qualitative research studies that yield valid and useful information. Examples of studies from a wide range of disciplines illustrate the strengths, limitations, and applications of the primary qualitative methods: in-depth interviews, focus group discussions, ethnography, content analysis, and case study and narrative research. Following a consistent format, chapters show students and researchers how to implement each method within a paradigm-neutral and flexible Total Quality Framework (TQF) comprising four interrelated components: Credibility, Analyzability, Transparency, and Usefulness. Unlike other texts that relegate quality issues to one or two chapters, detailed discussions of such crucial topics as construct validity, interresearcher reliability, researcher bias, and verification strategies are featured throughout. The book also addresses applications of the TQF to the writing, review, and evaluation of qualitative research proposals and manuscripts. Pedagogical Features: *Summary tables that highlight important content, such as the application of a method to vulnerable or hard-to-reach populations. *Case studies that illustrate TQF standards in practice for each method. *Guidelines for effective documentation (via thick descriptions) of each type of study. *End-of-chapter discussion topics, exercises, and suggested further reading and Web resources. *Chapters open with a preview and close with a bulleted summary of key ideas. *Extensive glossary"-- Provided by publisher. "This unique text provides a comprehensive framework for creating, managing, and interpreting qualitative research studies that yield valid and useful information. Examples of studies from a wide range of disciplines illustrate the strengths, limitations, and applications of the primary qualitative methods: in-depth interviews, focus group discussions, ethnography, content analysis, and case study and narrative research. Following a consistent format, chapters show students and researchers how to implement each method within a paradigm-neutral and flexible Total Quality Framework (TQF) comprising four interrelated components: Credibility, Analyzability, Transparency, and Usefulness. Unlike other texts that relegate quality issues to one or two chapters, detailed discussions of such crucial topics as construct validity, inter-researcher reliability, researcher bias, and verification strategies are featured throughout. The book also addresses applications of the TQF to the writing, review, and evaluation of qualitative research proposals and manuscripts. KEY WORDS/SUBJECT AREAS: case study, content analysis, ethnographic, ethnography, focus groups, interviews, narrative, proposal writing, qualitative research, reliability, research designs, research methods, standards, studies, the literacy, total quality framework, transparency AUDIENCE: Graduate students and instructors in education, sociology, psychology, social work, management, communications, and nursing; researchers and evaluators seeking guidance for their qualitative research work."--Publisher.
Machine generated contents note: 1. Making Sense of the Human Experience with Qualitative Research -- 1.1. Introduction -- 1.2. Unique Attributes Associated with Qualitative Research -- 1.3. The Total Quality Framework and the Reason for This Book -- 1.4. Overall Organization of the Book and Its Chapters -- 1.5. The Glossary -- 2. The Total Quality Framework -- Chapter Preview -- 2.1. Introduction -- 2.2. Paradigms and Frameworks -- 2.3. What Is the Total Quality Framework? -- 2.4. Applying the Total Quality Framework -- 2.5. Chapter Summary -- Suggested Further Reading -- 3. Interview Method: In-Depth Interviews -- Chapter Preview -- 3.1. Introduction -- 3.2. Four Modes of the In-Depth Interview Method -- 3.3. Applying the Total Quality Framework Approach to the In-Depth Interview Method -- 3.4. Chapter Summary -- 3.5. Exercises and Discussion Topics -- Suggested Further Reading -- Web Resource -- 4. Interview Method: Focus Group Discussions -- Chapter Preview -- 4.1. Introduction -- 4.2. Three Modes of the Group Discussion Method -- 4.3. Applying the Total Quality Framework Approach to the Group Discussion Method -- 4.4. Chapter Summary -- 4.5. Exercises and Discussion Topics -- Suggested Further Reading -- Web Resources -- 5. Observation Method: Ethnography -- Chapter Preview -- 5.1. Introduction -- 5.2. Ethnography in the Digital Age -- 5.3. Applying the Total Quality Framework Approach to Ethnography -- 5.4. Chapter Summary -- 5.5. Exercises and Discussion Topics -- Suggested Further Reading -- Web Resources -- 6. Qualitative Content Analysis -- Chapter Preview -- 6.1. Introduction -- 6.2. Computer-Assisted Qualitative Content Analysis -- 6.3. Applying the Total Quality Framework Approach to Qualitative Content Analysis -- 6.4. Chapter Summary -- 6.5. Exercises and Discussion Topics -- Web Resources -- 7. Multiple Methods in Case-Centered Approaches: Case Study and Narrative Research -- Chapter Preview -- 7.1. Introduction -- 7.2. Process in Case-Centered Research -- 7.3. The Total Quality Framework Approach to Case-Centered Research -- 7.4. Chapter Summary -- 7.5. Exercises and Discussion Topics -- Suggested Further Reading -- Web Resource -- 8. The Total Quality Framework Research Proposal and Other Practical Applications of the Total Quality Framework -- Chapter Preview -- 8.1. Introduction -- 8.2. Section-by-Section Discussion of the Total Quality Framework Research Proposal -- 8.3. Evaluating Proposals Using the Total Quality Framework -- 8.4. Related Uses of the Total Quality Framework in Reviewing Research Reports -- 8.5. Chapter Summary -- Glossary -- References -- Author Index -- Subject Index -- About the Authors.
Includes bibliographical references (pages 365-379) and indexes.
Keywords: Social sciences -- Research -- Methodology; Qualitative research; Research -- Methodology